Fossil record of stem groups employed in evaluating the chronogram of insects (Arthropoda: Hexapoda) - Wang, Yan-hui (Sci Rep, 2016)
Insecta s. str. (=Ectognatha), comprise the largest and most diversified group of living organisms, accounting for roughly half of the biodiversity on Earth. Understanding insect relationships and the specific time intervals for their episodes of radiation and extinction are critical to any comprehensive perspective on evolutionary events. Although some deeper nodes have been resolved congruently, the complete evolution of insects has remained obscure due to the lack of direct fossil evidence. Besides, various evolutionary phases of insects and the corresponding driving forces of diversification remain to be recognized. In this study, a comprehensive sample of all insect orders was used to reconstruct their phylogenetic relationships and estimate deep divergences. The phylogenetic relationships of insect orders were congruently recovered by Bayesian inference and maximum likelihood analyses. A complete timescale of divergences based on an uncorrelated log-normal relaxed clock model was established among all lineages of winged insects. The inferred timescale for various nodes are congruent with major historical events including the increase of atmospheric oxygen in the Late Silurian and earliest Devonian, the radiation of vascular plants in the Devonian, and with the available fossil record of the stem groups to various insect lineages in the Devonian and Carboniferous.